(untitled) - Alberta Law Reform Institute (Edmonton, 2000)
In the book, the author recommended that Alberta enact a modern class actions statute based on the Canadian model that has been enacted in Quebec, Ontario and British Columbia. Our recommendations are based on the prototype of this model contained in the Uniform Class Proceedings Act adopted by the Uniform Law Conference of Canada in 1996. They are intended to: improve access to justice for persons whose actions have merit but might not otherwise be asserted because of litigation costs; contribute to judicial economy by better containing costs to litigants and the court system and otherwise expediting judicial proceedings; and in providing greater access to justice, help deter wrongful conduct by making sanctions available.
Keywords: Class actions (Civil procedure); Khởi tố tập thể (Quy trình dân sự); Alberta